ASIMETRI INFORMASI SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN DAN KEJELASAN SASARAN ANGGARAN PADA SENJANGAN ANGGARAN - Mirda Yanti, Ni Wayan; Ratna Sari, Maria M. (E-Jurnal Akuntansi, 2016)
The budget is fundamental for an organization to run the operations of the institution. This research aims to determine the effect of budgetary participation and budget goal clarity on the budgetary slack is moderated by asymmetry of information. Research on 43 SKPD Tabanan. Sample selection is done by using a sampling method saturated. Total respondents 129 people consisting of Chief SKPD, Head of Sub. General and Planning and Head of the sub. Financial department. The analysis technique used is multiple linear regression analysis and Moderated Regression Analysis. The study found that the participation budgeting positive influence on budgetary slack, budget goal clarity positive influence on budgetary slack, the information asymmetry strengthen budgetary participation influence on budgetary slack, and the information asymmetry does not moderate the effect of budget goal clarity on budgetary slack.
Keywords: budgetary slack, participation budgeting, budget goal clarity, information asymmetry